Conundrum in Measured Electron Affinities of Complex Heavy Atoms - Felfli, Zineb; Msezane, Alfred Z. (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2018)
Low-energy electron scattering from the lanthanide atoms Eu, Tb, Tm, Gd, and Nd including Nb is investigated through calculated electron elastic total cross sections using our robust Regge-pole methodology. The extracted binding energies of the resultant ground and metastable anions formed during the collisions are contrasted with the measured electron affinities (EAs). It is concluded that the measured EAs for these atoms require reinterpretation and new recommended values are presented.